p53 Expression in Gallbladder Lesions: A Cross-sectional Study from a Tertiary Care Centre in Northern India - Nazia Manzoor Walvir; Zubaida Rasool; Subrina Masoodi; Ashfaq ul Hassan; Abrar Habib Lone; Inara Abeer (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Gallbladder lesions comprise inflammatory, benign, pre-malignant, and malignant lesions. The progression of benign lesions into malignant ones involves a complex process. The p53 gene is commonly disrupted in carcinogenesis. Malignant lesions may exhibit p53 overexpression compared to benign and inflammatory lesions. Aim: To investigate the distribution of gallbladder lesions and the expression of the p53 nuclear protein in these lesions. Materials and Methods: A cross-sectional study was conducted at the Department of Pathology, Sher-i-Kashmir Institute of Medical Sciences, Srinagar, Jammu and Kashmir, from June 2020 to December 2022. A total of 249 specimens of gallbladder lesions, including congenital, inflammatory, benign, pre-malignant, and malignant lesions, were included. All samples underwent Haematoxylin & Eosin(H&E) staining and Immunohistochemistry (IHC) with p53 antibody using the peroxidase-antiperoxidase method. The association of P53 expression with histopathological diagnosis was analysed using Fisher’s Exact test. The final analysis was performed using Statistical Package for Social Sciences (SPSS) software, version 25.0. A p-value <0.05 was considered statistically significant. Results: Out of 249 specimens, there were 217 (87.14%) inflammatory lesions, 9 (3.6%) benign lesions, 2 (0.8%) premalignant lesions, and 21 (9.26%) malignant lesions. The main inflammatory lesions were Chronic Cholecystitis (CC) with 132 cases (60.83%) and CC with cholesterosis with 36 cases (16.59%). The most common pre-malignant lesion was choledochal cyst with 3 cases (3.33%). Benign tumours (leiomyoma) were present in 2 (0.8%) patients. Among the 21 (8.46%) malignant tumours, 4 (19.05%) were moderately differentiated adenocarcinoma, 13 (61.9%) were poorly differentiated adenocarcinoma, and 4 (19.05%) were welldifferentiated adenocarcinoma. P53 overexpression was significantly higher in patients with malignant tumours (9 cases, 42.86%) compared to inflammatory lesions (26 cases, 11.98%), benign lesions (0 cases, 0%), and pre-malignant lesions (0 cases, 0%) (p=0.003). Conclusion: Gallbladder lesions exhibit a wide range of histopathological presentations. Inflammatory lesions are the most common, followed by pre-malignant and malignant lesions. P53 can serve as a novel marker for differentiating inflammatory lesions from malignant lesions in the gallbladder.